PENERAPAN KETERAMPILAN MENGAJAR EFEKTIF UNTUK MEMACU MOTIVASI BELAJAR: Peran Keterampilan Mengajar yang Efektif dalam Meningkatkan Motivasi Belajar Siswa: Studi Kasus di Sekolah Menengah Atas Cempaka Putih - Amelia, Shela; Sadillah, Sadillah; Syihab, Ridho Azkaning; Firdaus, Rafli; Alfarisi, Salman (Edukasi: Journal of Educational Research, 2024)
This study aims to explore the application of effective teaching skills as a strategic effort to enhance student learning motivation at the senior high school level. The research is motivated by the declining student engagement in various learning settings, particularly in the post-pandemic era, where learning motivation is a crucial yet often overlooked factor. Employing a qualitative descriptive approach, the study was conducted at SMA Cempaka Putih using observations, interviews, and documentation as data collection techniques. Thematic analysis was applied to identify patterns of teaching practices and their impact on students' motivational responses. The findings reveal that key teaching competencies—such as clear communication, instructional variation, positive reinforcement, and classroom management—are strongly correlated with increased student participation, confidence, and intrinsic motivation. The study implies that empowering teachers with pedagogical skills that address students' cognitive, emotional, and social needs is essential in fostering a productive learning environment. This research contributes original insights by providing an in-depth contextual understanding of how effective teaching behaviors manifest in real classroom settings and how they shape students' motivational dynamics.